2019
DOI: 10.1016/j.sjbs.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of olive leaves extract on hepatorenal injury in streptozotocin diabetic rats

Abstract: Medicinal plants have always been an important source of new alternative effective compounds for human therapy. Currently, there are many of scientific evidences indicate that the medicinal plants contain a lot of hypoglycemic chemical compounds. The purpose of the present study was to determine the influence of olive leaves extract on hepatorenal injury in diabetic male rats. Experimental diabetes was induced by streptozotocin (STZ). The levels of serum glucose, alanine aminotransferase, aspartate aminotransf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…This study is consistent with previous studies that showed that an inverse relationship between vegetable intake and 2-hour glucose concentration in OGTT was found, but the analyses were only adjusted for cohort, age, BMI, and energy intake [29]. Also in a crosssectional study of a Canadian native population a protective effect of vegetables on impaired glucose tolerance or T2D was reported [30].…”
Section: Discussionsupporting
confidence: 92%
“…This study is consistent with previous studies that showed that an inverse relationship between vegetable intake and 2-hour glucose concentration in OGTT was found, but the analyses were only adjusted for cohort, age, BMI, and energy intake [29]. Also in a crosssectional study of a Canadian native population a protective effect of vegetables on impaired glucose tolerance or T2D was reported [30].…”
Section: Discussionsupporting
confidence: 92%
“…BUN and creatinine are both excreted by the kidney. Hence, impairment of kidney function results in the accumulation of BUN and creatinine in the blood (Al‐Attar & Alsalmi, 2017). Treatment with T. triandra caused a decrease in the BUN and creatinine levels.…”
Section: Discussionmentioning
confidence: 99%
“…al., 2016). Antioxidant activities of the olive leaf extracts played a fundamental role against the renal damage induced by diabetes (Al-Attar and Alsalmi, 2019b). These studies were confirmed by the study of Ağgül et.…”
Section: Discussionmentioning
confidence: 63%